Strategi Bertahan di Masa Pandemi Covid-19 dalam Perseptif Ekonomi Islam - Mochammad Nurfaiz Muzakki; Kholifatul Husna Asri (ALIF, 2022)
The purpose of this study was to determine the impact of MSMEs on the income of the community in an Islamic perspective, and also find out how the strategies of micro, small and medium enterprises (MSMEs) can survive in the Covid-19 pandemic. This study was a field research based on qualitative methods. The results showed that MSMEs in Telukpinang village are able to contribute to the surrounding residents, namely by providing jobs. This clearly gives welfare to the community in general and especially to the owner. Micro, Small, and Medium Enterprises (MSMEs) are a strategic economic sector and involve the livelihoods of many people, thus affecting the national economy. In the Islamic economic perspectives, UMKM is a legalized economic activity. There is no prohibition as long as the business being carried out does not deviate from the Islamic religion. The sustainability and existence of the MSME business is influenced by two factors, namely internal factors in the form of economic motives while external factors in the form of the economic environment which are usually used as a person's life theme. In addition, during a pandemic like today, business owners must have a strategy so that their business continues and does not suffer too large losses. No exception sharia business owners must also have a strategy so that Micro, Small and Medium Enterprises are able to recover economic shocks during the Covid-19 pandemic.